Pengaruh Kualitas Pelayanan, Customer Value, Image, dan Pemasaran Relasional terhadap Kepuasan Pelanggan - Mustaan Mustaan; Nizar Hamdi (Valid: Jurnal Ilmiah, 2021)
Research objectives are to describe the quality of services, customer value, image and marketing relational and customer satisfaction. Analyze the influence of the quality of services, customer value, image, and marketing relational to customer satisfaction. In addition to analyzing the quality of services, customer value, image, and marketing relational an influential dominant to customer satisfaction in university students merdeka poor. This research in a survey with a population of 1.347 people and sample of 135 people, technique collection respondents had to use technique census. Test an instrument use the validity, reliability test. Technique analysis data using descriptive analysis, test the assumption classical, linear regression multiple, the hypothesis or test, t-test and f test with a significant degree of 5 %. The research results show simultaneously the quality of services, customer value, image, and marketing relational there are strong relationship and influential significant impact on customer satisfaction, the results of the analysis in partial the quality of services, customer value, image, and marketing relational significant to customer satisfaction. The results of the analysis R2adjusted value of 33.0 % suggests the contribution of the quality of services, customer value, image, and marketing relational to customer satisfaction while by 67% influenced other variables such as a product, the price, place, promotion, distribution, perception value and others